Effects Of Irrigation Scheduling And Soil Management On Maize (Zea Mays L.) Yield In Guinea Savannah Zone Of Nigeria - I. Alhassan; A. M. Saddiq; A. G. Gashua; K. K. Gwio-Kura (Zenodo, 2017)
The main objective of any irrigation program is the development of an efficient water management system to sustain crop growth and development and avoid physiological water stress in the growing plants. Field experiment to evaluate the effects of some soil moisture conservation practices on yield and water use efficiency (WUE) of maize was carried out in three locations (i.e. Mubi and Yola in the northern Guinea Savannah and Ganye in the southern Guinea Savannah of Adamawa State, Nigeria) during the dry seasons of 2013 and 2014. The experiment consisted of three different irrigation levels (7, 10 and 12 day irrigation intervals), two levels of mulch (mulch and un-mulched) and two tillage practices (no tillage and minimum tillage) arranged in a randomized complete block design with split-split plot arrangement and replicated three times. The Blaney-Criddle method was used for measuring crop evapotranspiration. The results indicated that seven-day irrigation intervals and mulched treatment were found to have significant effect (P>0.05) on grain yield and water use efficiency in all the locations. The main effect of tillage was non-significant (P<0.05) on grain yield and WUE. The interaction effects of irrigation and mulch were significant (P>0.05) on grain yield and WUE at Mubi and Yola. Generally, higher grain yield and WUE were recorded on mulched and seven-day irrigation intervals, whereas lower values were recorded on un-mulched with 12-day irrigation intervals. Tillage exerts little influence on the yield and WUE. Results from Ganye were found to be generally higher than those recorded in Mubi and Yola; it also showed that an irrigation interval of 10 days with mulching could be adopted for the Ganye area, while seven days interval is more appropriate for Mubi and Yola. : {"references": ["FAO, Reforming water resources policy - A guide to methods, processes and practices - FAO irrigation and drainage paper 52, 1995", "FAO/IAEA, Agriculture Water Management - for Improving Crop Productivity, Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture, Vienna International Centre, PO Box 100 A-1400 Vienna, Austria, 2014. http://www-naweb.iaea.org/nafa/swmn/topic-water-management.html. Accessed on 29/09/2016", "S. P. Bhardwaj and N.S. Sindhwal, \"Zero tillage and weed mulch for erosion control on sloping farmland in Doon Valley\", Indian Journal of Soil Conservation, vol. 26, pp. 81-85, 1998.", "J. Liu, S.A. Xu, G.Y. Zhou and H.H. Lu, \"Effect of transplanting multi-cropping spring maize with plastic film mulching on the ecological effect, plant growth and grain yield,\" Journal of Hubei Agriculture College, vol. 2, pp. 97-100, 2002", "L. Edwards, J. R. Burney, G. Richter, A. H. MacRae, \"Evaluation of compost and straw mulching on soil-loss characteristics in erosion plots of potatoes in Prince Edward Island,\" Canadian Agricultural Ecosystem Environment, vol. 81, no. 3, pp. 217-222, November, 2000.", "S. O. Ojeniyi, S. Odedina, J. Odedina, M. Akinola, \"Effect of tillage and mulch combination on soil physical properties and sorghum performance on soil physical properties and sorghum performance on alfisol of southwest Nigeria,\" Nigerian Journal of Soil Science, vol. 19, no. 2, pp. 2009.", "A. C. Guzha, Effects of tillage on soil microrelief surface depression storage and soil water storage. Soil Tillage Research, vol. 76, pp105\u2013114, 2004.", "G. Rouanet, The Tropical Agriculturist, Maize. Macmillan Publishers, 1987, pp. 23-27", "B. H. Usman, \"The Soils of Adamawa State, North Eastern Nigeria\" in Agriculture in Adamawa State, E. C. Igwe; S. I. Mshelia and M. Y. Jada, Eds, Paraclete Publishers Yola, Nigeria, 2005, pp. 62-83.\n[10]\tAdamawa State Agricultural Development Programme, Evaluation Department, Yola Adamawa State, Nigeria. Meteorological Data for 2013-2014\n[11]\tP. C. Jaiswal, Soil, Plant and Water Analysis, Kalyani Publishers, New Delhi, 2011.\n[12]\tR. Li, X. Q. Hou, Z. K. Jia, X. L. Ren and B. P. Yang, Effects on soil temperature, moisture, and maize yield of cultivation with ridge and furrow mulching in the rainfed area of the Loess Plateau, China, Agricultural Water Management, vol. no. 116, pp. 101\u2013109, 2013. doi:10.1016/j.agwat.2012.10.001\n[13]\tC. Brouwer and M. Heibloem, Irrigation Water Management: Irrigation Water Needs, Food and Agriculture Organization of the United Nations, Training manual no. 3, 1986.\n[14]\tR.G. Allen, L.S. Pereira, D. Raes and M. Smith, 'Crop evapotranspiration \u2013Guidelines for computing crop water requirements', FAO Irrigation and Drainage Paper 56, 1998.\n[15]\tG. Stanhill, Water use efficiency, Advances in Agronomy, vol. 39, pp. 53 \u201385, 1986. doi:10.1016/S0065-2113(08)60465-4\n[16]\tGenStat Discovery Edition 3, VSN International Ltd., Hemel Hempstead, UK, 2007.\n[17]\tF. Bearnaert and D. Bitondo, A Simple and Practical Method to Evaluate Analytical Data of Soil Profiles, CUDs, Soil Science Department, Belgian Cooperation Dschang Cameroon, 1992, pp. 65.\n[18]\tJ. A. Tolk, T. A. Howell and S. R. Evett, \"Effect of mulch, irrigation and soil type on water use and yield of maize,\" Soil and Tillage Research, vol. 50, no. 2, pp. 137-147, March, 1999. doi.org/10.1016/S0167-1987(99)00011-2\n[19]\tR. Yaseen, J. Shafi, W. Ahmad, M. S. Rana, M. Salim and S W. V. Averbeke and J. N. Marais, \"Maize response to plant population and soil water supply. I. Yield of grain and total above ground biomass,\" South African Journal of Plant and Soil, vol. 9. no. 4, pp. 186-192, 1992.\n[20]\tA. Qaisrani, \"Effect of Deficit Irrigation and Mulch on Soil Physical Properties, Growth and Yield of Maize,\" Environment and Ecology Research, vol. 2, no. 3, pp. 122-137, March, 2014. doi: 10.13189/eer.2014.020302\n[21]\tT. Oweis, M. Pala, J. Ryan, \"Stabilizing rainfed wheat yields with supplemental irrigation and nitrogen in a Mediterranean climate,\" Agronomy Journal, vol. 90, no. 5, pp. 672\u2013681, September, 1998. doi:10.2134/agronj1998.00021962009000050017x"]}